Research priorities for parenting and child health: a Delphi study - Hauck, Yvonne; Kelly, R.; Fenwick, Jennifer (Blackwell Publishing Ltd, 2007)
Research priorities for parenting and child health: a Delphi study. Aim. This paper is a report of a study to identify research priorities of clinical staff working with families at a Western Australian centre for parenting. Background. Australian centres for parenting focus on children's needs while working in partnership with parents, with parents, families and their communities. These agencies incorporate primary healthcare strategies in their unique approach with families. Clinician's research priorities at these centres have not been explored in an Australian context. Method. In 2005, a Delphi study was conducted in which clinicians were asked to provide a list of five important issues relating to care provided to children, parents and their families. Research topics identified were then ranked for their importance to the family and clinicians. Finally, the top 10 research topics were ranked for priority. Findings. In round 1, 148 research topics were identified. Thirty-six topics were removed, due to the availability of existing evidence. Content analysis was used to collapse statements into 26 research questions, which were further classified into seven categories: parenting issues; sleep and settling issues; postnatal depression; evaluation and impact of programmes; staffing issues; centre marketing services and others. Issues relating to sleep and settling and postnatal depression were rated as top research priorities. Conclusion. The priorities of clinicians working with families provide research direction for this Western Australian centre and potentially other centres in Australia and similar settings elsewhere in the world. The Delphi approach in determining 'clinicians' perceptions of relevant research areas may be useful to direct research in other contexts.